The influence of educational information visualization trends in higher education for students in the Russian Federation - Matveeva, Natalya; Dorel, Lea; Kosareva, Irina; Sabirova, Fairuza (Frontiers in Education, 2023)
The establishment of scientific foundations for the integration of information technologies and innovative educational processes in student learning activities entails the necessity of creating a basis for transitioning from information processes to information technologies. The research aims to study the effectiveness of innovative information technologies in higher education and assess student involvement in using innovative information technologies. The study relies on the experimental method to survey to assess respondents' involvement in the use of innovative information technologies. In addition, the modeling method was used to increase students' motivation to study through visualization and other modern technologies. A training program based on visualization and innovative information technologies aimed to study their impact on the teaching process in higher education was developed. The study results show that visualization technologies improve students' intrinsic motivation to learn. The practical significance and further research prospects are due to the possibility of applying the training program developed in the study in higher education. The program can also become the basis for developing new training programs to study other subjects as it is not tied to studying a certain discipline and requires only computer skills.